Ethical attitudes of the future Russian officials and businessmen: Comparative analysis - A. A. Maksimenko; O. S. Deyneka; D. V. Krylova; E. V. Zabelina; E. A. Bulgakova (Russian State Vocational Pedagogical University, 2023)
Introduction. In accordance with the Bucharest Declaration of Ethical Values and Principles of Higher Education (2004), modern universities cannot be considered only as scientific and technical "factories" in isolation from values and ethical norms. In accordance with their mission in society, they should "contribute in every possible way to the establishment and inculcation of the highest moral standards".In this article, the problem of training future government and municipal employees in the Russian universities of the country is actualised based on the analysis of the research results of their ethical attitudes in order to indirectly assess the effectiveness of anti-corruption training of students of specialised educational programmes in the areas of "Government and Municipal Administration" and "Law".Aim. The present empirical study aimed to identify the ethical attitudes of future officials in comparison with future entrepreneurs, as well as with the employees of commercial companies and government officials.Methodology and research methods. The authors conducted an online research. The research involved 874 people. The main test sample (134 students) consisted of two groups: students of the speciality "Government and Municipal Administration" and "Law" (70 people), and students of business education programmes (64 people). The background sample consisted of the government and municipal employees (39.0% of the total sample) and the employees of commercial companies (36.5%), as well as the representatives of NGOs (6.8%). In the course of a comparative study, using the questionnaire "Moral Views (Amoralism)-2" by E. A. Bulgakova, and the scale of the "Dark Future" by Z. Zalessky, the authors tested the hypothesis on the samples of future officials and future business representatives. The tested hypothesis was based on some works of foreign authors and consisted of the fact that future Russian entrepreneurs were expected to have a higher degree of relativism (than future officials), supporting personal moral standards and rejecting universal moral principles.Results. The tested hypothesis was not confirmed by the research results. Compared to future entrepreneurs, future officials are significantly more likely to justify the act of appropriation, deception due to omissions, and revenge within the law. Future officials turned out to have higher indicators on the scales of cynicism, aggressiveness and hostility than students in the field of business education. In addition, future civil servants have more uncertainty about whether they will be able to take place in life, fears about possible collisions with life crises and difficulties, as well as anxiety for their future. Existing university ethics training programmes often only strengthen relativistic views and form deviant behaviour in the future.Scientific novelty. The scientific novelty of the study consists in the fact that the authors carried out theoretical analysis and empirical research, which consisted in the study of ethical attitudes among the representatives of two professional groups.Practical significance. As part of the development of training programmes, it is advisable to increase the emphasis on structurally mature ethical attitudes of professionals, especially state and municipal employees.